Visitors’ preferences on recreational activities at Polumpung Melangkap view campsite - Juriaman, Mohd Fariz (2019)
Recreational Activities is an outdoor activity that has attracted the attention of locals and general coverage in the mass media, especially in social media lately. However, the issue regard to recreational activities nowadays is many people are less doing recreational activities at this time. Therefore, this study will examine the relative importance of recreational activities and the level of satisfaction with the activities and facilities provided PMVCS. There are two objectives in this study: i) to identify the potential of recreational activities preferred by visitors at PMVCS, Kota Belud ii) to provide information on the most demanding recreational facilities at PMVCS, Kota Belud. The study of this research was an exploratory approach by applying quantitative methods as the main research method. Respondents of this study consist of 150 visitors at Polumpung Melangkap View Camp Site Kota Belud, Sabah. The data collection techniques used are questionnaire and indirect interview with the employers. The results show that there are some attraction factors that encourage respondents to do recreational activities, i.e. clear and cool river water, the beauty of the scenic view, the activities provided and the location. Furthermore, respondents' satisfaction levels on activities provided at PMVCS such as river bathing activities, photography activities, scenic view activities, picnic activities, and videography activities. In addition, the highest demand for facilities available at PMVCS is a camping facilities, water facilities and equipment for rent such as tents, cooking utensils, tables and more. In conclusion, this study is useful for the entrepreneurs in particular, as well as future researchers and as well as policy makers to ensure camping camp in Sabah especially in Kota Belud is more advanced and well-known at higher level.